Unilateral NMR: a Noninvasive Tool for Monitoring In Situ the Effectiveness of Intervention to Reduce the Capillary Raise of Water in an Ancient Deteriorated Wall Painting. (22nd January 2012) - Di Tullio Di Tullio, Valeria Valeria; Proietti Proietti, Noemi Noemi; Gentile Gentile, Gennaro Gennaro; Giani Giani, Elisabetta Elisabetta; Poggi Poggi, Domenico Domenico; Capitani Capitani, Donatella Donatella
Abstract : Portable unilateral NMR was used to quantitatively map in a fully noninvasive way the moisture distribution in an ancient deteriorated wall painting before and after an intervention to reduce the capillary raise of water through the wall. Maps obtained at a depth of 0.5 cm clearly showed the path of the capillary raise and indicated that, after the intervention, the moisture level was reduced. Maps obtained by measuring the first layers of the wall painting were affected by the critical environmental conditions of the second hypogeous level of St. Clement Basilica, Rome, and by the presence of salts efflorescence and encrustations on the surface of the wall painting. The morphology and the elemental composition of salts investigated by SEM-EDS indicated that efflorescences and encrustations were mostly constituted of gypsum and calcite. The presence of these salts is explained with the presence of high concentration of carbon dioxide and sulphur-rich particles due to pollution which, along with the high-moisture level and the extremely feeble air circulation, cause recarbonation and sulphation processes on the plaster surface.